Chromobacterium violaceum infection in a free ranging howler monkey in Costa Rica - Baldi, Mario (2010)
Chromobacterium violaceum is a gram-negative saprobe bacterium that is a rare opportunistic pathogen in mammals. There are numerous reports in humans including fatalities, but no record exists in free-ranging nonhuman primates. Here we report an infection by C. violaceum in a wild adult male howler monkey (Alouatta palliata) captured at Ballena Marine National Park, in southwestern Costa Rica. The individual had severe skin lesions over its extremities; gross findings included multiple skin ulcers, white foci in liver, and lymphoid hyperplasia. Histologic results included deep dermatitis with presence of necrotic epithelial cells where clusters of coccoid-shaped bacteria were detected. In the liver, numerous neutrophils forming microabscesses, telangiectasia, and focal necrotic areas were observed. Necrotic liver tissue sampled for bacteriologic culture resulted in the isolation of C. violaceum. We could not ascertain the source or mechanism of infection in this case, although infection through skin microabrasions is suspected. To the best of our knowledge, this is the first report for this pathogen in a wild, nonhuman primate. This report also draws attention to this infectious agent as a potential emerging wildlife disease and consideration should be paid by regional veterinary and epidemiologic vigilance services.